Regional Entrepreneurship and Innovation Management: Actors, Helices and Consensus Space - TODEVA, Emanuela; KETIKIDIS, Panagiotis (Management Dynamics in the Knowledge Economy, 2017)
European Smart Specialization (S3) policies aim to mobilize innovation and entrepreneurial capabilities and to deliver job creation and economic growth through inter-regional cooperation. The foundation principles for this policy initiative are an entrepreneurial discovery process that aims to mobilize all stakeholders throughout all stages from conception to strategy implementation; government-led policy initiatives for selecting strategic investment priorities; and building triple helix consensus space for regional policy and strategy implementation. However, the key existing gap resides in a proper investigation of such a consensus space that would fulfill the S3 mission. In this context, this paper outlines the key developments in regional innovation and entrepreneurship that have emerged through the process of S3 development and implementation. The discussion starts with an overview of the challenges and barriers and policy response for building place-based consensus space. We look at critical questions that are addressed by national and regional authorities and the localized mobilization of entrepreneurial and innovation capabilities. Our analysis of the regional innovation and entrepreneurial systems focuses on individual actors within the triple helix model of university-industry and government and their interaction for building a consensus space. We conclude the paper with recommendations for enhanced facilitation and orchestration of inter-regional value chains.